ON THE CALCULATION OF TRUE ENERGY OF THE GRAVITATIONAL FIELD IN GR - Murzagaliev, G. Zh.; Komarov, A. A. (Recent Contributions to Physics, 2011)
The possibility to define the true energy of the gravitational field in external Schwarzschild’ problem is treated on the basis of energy-momentum pseudotensor.